Semiotic Analysis of Cultural Identity and Colonial Resistance in “Black Panther: Wakanda Forever” - Hafitri, Erlania; Rahmawati, Laili Etika (LPPM Stikosa - AWS, 2025)
Film is one of the mass communication media, producing and displaying a message or ideology. This study aims to analyze the representation of culture and resistance to colonialism in the film Black Panther: Wakanda Forever using Roland Barthes' semiotic approach in a Qualitative method. Data were obtained from selected scenes that display visual symbols such as hand gesture symbols, spiritual interactions with ancestors, conversations between characters, costume that shows culture, and women's leadership and traditional-modern technology. The results of this study are 1) women's emancipation through female figures who lead and are strong to break the stigma of weak women and challenging subordinative stereotypes 2) culture as an element and foundation for forming identity reflected in language, costume, architecture, and spiritual traditions 3) the film builds a counter-narrative to the colonial view by repositioning Africa and Mesoamerica as advanced, sovereign, and spiritually valuable regions. This representation shows that cultural identity and communal solidarity are the main forces in facing neocolonial domination. These findings contribute to media and cultural studies by highlighting how popular films can be a medium for the articulation of postcolonial ideology and symbolic resistance through visual narratives.